2015
DOI: 10.1097/olq.0000000000000363
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Introducing Triage Criteria for Express Testing at a Canadian Sexually Transmitted Infection Clinic

Abstract: The implementation of express testing in an sexually transmitted infection (STI) clinic reduced the length of visit time compared with other visit types and increased the proportion of STIs diagnosed at clinic visits. Express testing did not impact the time to treatment for asymptomatic patients diagnosed as having an STI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 9 publications
0
22
0
Order By: Relevance
“…In settings where self-testing programs are not yet available, implementing new testing policies and programs can help in diagnosing infections quickly and reduce infection duration. Gratrix et al 17 implemented an express testing criterion at a Canadian STI clinic where patients who reported being asymptomatic, had not had a contact of an STI, had not had receptive anal intercourse since their last testing visit, and had no history of sexual assault in the last 2 weeks were able to forgo a physical examination and receive STI/HIV testing. Through this program, there was a significant increase in the diagnosis of chlamydia, gonorrhea, and syphilis infections compared with standard of care.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In settings where self-testing programs are not yet available, implementing new testing policies and programs can help in diagnosing infections quickly and reduce infection duration. Gratrix et al 17 implemented an express testing criterion at a Canadian STI clinic where patients who reported being asymptomatic, had not had a contact of an STI, had not had receptive anal intercourse since their last testing visit, and had no history of sexual assault in the last 2 weeks were able to forgo a physical examination and receive STI/HIV testing. Through this program, there was a significant increase in the diagnosis of chlamydia, gonorrhea, and syphilis infections compared with standard of care.…”
Section: Resultsmentioning
confidence: 99%
“…For practices that are not equipped to implement POC NAAT tests, self-sampling has shown to be cost-effective when implementing new STI screening programs. Gratrix et al 17 reported on the implementation of triage criteria for express visits with self-sampling at a Canadian STI clinic. This program saved approximately CA$7.41 per male visit and CA$10.55 per female visits, resulting in cost savings estimated at CA$40,000 over the course of the 13-month study.…”
Section: Resultsmentioning
confidence: 99%
“…80 Triaging patients who do not require clinical examination or immediate treatment is a highly effective method to increase the number of patients receiving testing and freeing up clinical resources for those whose symptoms are suggestive of a STI or in whom guidelines might recommend immediate assessment and treatment; for example, those presenting because a sexual contact has been diagnosed with an STI. 81,82…”
Section: Service Efficiency and Effectivenessmentioning
confidence: 99%
“…64,65 Self-obtained specimens for testing gonorrhoea and chlamydia and 'express visits' for routine asymptomatic screening can be widely implemented to increase efficiency, reduce long-term costs and reduce visit lengths. [66][67][68][69][70][71][72] Twenty-one percent of visits to specialised SHCs in the US were express STI or HIV testing-only visits, suggesting a large proportion of asymptomatic screenings can be accomplished without lengthy face-to-face consultation and in some areas, the need to see a clinician. 30 Lean service delivery models for high throughput and low barrier clinics for HIV/STI testing have been initiated to address increased volume and demand.…”
Section: Improving Clinic Efficiency and Decreasing Barriers To Carementioning
confidence: 99%